PELATIHAN PEMBUATAN KAIN JUMPUTAN/BATIK DI TK. QURRATA A’YUN DI CIMAHI KOTA CIMAHI - Luciana Luciana; Feny Nurherawati (LPPM IST AKPRIND Yogyakarta, 2020)
Jumputan batik is batik made by tie and dyeing techniques with the desired motif and color.There are two techniques of making jumputan batik, the first is with the tie technique, andthe second is the sewing technique, the threads used to tie the fabric should be made of thickand strong threads, so that they can prevent dyes from entering the fabric, such as plastic /synthetic threads. jeans floss, or shoe thread. The method used in this community serviceactivity is counseling (socialization) and the practice of making batik which is carried outon students who are accompanied by the students' parents at Qurrata A'yun CimahiKindergarten. This activity is not only aimed at training students' creativity, which is shownby the creation of the tie and coloring of each batik they produce and is also expected tomotivate parents of students to gain new knowledge and be able to produce products thathave high use value and selling value, so that they can be an opportunity to improve theeconomy.